Construction of acetyl-CoA and DBAT hybrid metabolic pathway for acetylation of 10-deacetylbaccatin III to baccatin III - Hao Wang; Bo-Yong Zhang; Ting Gong; Tian-Jiao Chen; Jing-Jing Chen; Jin-Ling Yang; Ping Zhu (Elsevier, 2021)
10-Deacetylbaccatin III (10-DAB) C10 acetylation is an indispensable procedure for Taxol semi-synthesis, which often requires harsh conditions. 10-Deacetylbaccatin III-10-β-O-acetyltransferase (DBAT) catalyzes the acetylation but acetyl-CoA supply remains a key limiting factor. Here we refactored the innate biosynthetic pathway of acetyl-CoA in Escherichia coli and obtained a chassis with acetyl-CoA productivity over three times higher than that of the host cell. Then, we constructed a microbial cell factory by introducing DBAT gene into this chassis for efficiently converting 10-DAB into baccatin III. We found that baccatin III could be efficiently deacetylated into 10-DAB by DBAT with CoASH and K+ under alkaline condition. Thus, we fed acetic acid to the engineered strain both for serving as a substrate of acetyl-CoA biosynthesis and for alleviating the deacetylation of baccatin III. The fermentation conditions were optimized and the baccatin III titers reached 2, 3 and 4.6 g/L, respectively, in a 3-L bioreactor culture when 2, 3 and 6 g/L of 10-DAB were supplied. Our study provides an environment-friendly approach for the large scale 10-DAB acetylation without addition of acetyl-CoA in the industrial Taxol semi-synthesis. The finding of DBAT deacetylase activity may broaden its application in the structural modification of pharmaceutically important lead compounds.